Electrical resistivity of Ni-Fe wires coated with sn using low-pressure chemical vapor deposition - Kim, Jun Hyun; Bak, Jeong Geun; Kim, Chang Koo (Coatings, 2020)
In this study, we demonstrated that the deposition of Sn on Ni-Fe wires using low-pressure chemical vapor deposition (LPCVD) can be used to control the electrical resistivity of the wires. Furthermore, the effect of the deposition temperature on the resistivity of the Ni-Fe wires was investigated. The resistivity of the Sn-deposited Ni-Fe wires was found to increase monotonically with the deposition temperature from 550 to 850 °C. Structural and morphological analyses revealed that electron scattering by Ni3Sn2 and Fe3Sn particulates, which were the reaction products of LPCVD of Sn on the surface of the Ni-Fe wires, was the cause of the resistivity increase. These coalesced particulates displayed irregular shapes with an increase in the deposition temperature, and their size increased with the deposition temperature. Owing to these particulate characteristics, the Sn content increased with the deposition temperature. Furthermore, the temperature dependency of the Sn content followed a pattern very similar to that of the resistivity, indicating that the atomic content of Sn directly affected the resistivity of the Ni-Fe wires.
Keywords: Electrical resistivity; Fusing resistor; LPCVD; Ni-Fe wire; Sn